Root Cause Analysis: Simplified Tools and Techniques - Bjørn Andersen; Tom Fagerhaug (USA ASQ Quality Press, 2006)
The use of quality and continual improvement is no longer considered the sole property of manufacturing or of the traditional engineering and production environment. Most professionals entering the workforce today are required to analyze situations, identify problems, and provide solutions for improved performance. Improving the organization is everyone s job. Teamwork is critical, requiring the participation of members of all backgrounds, nationalities, educational levels, and career aspirations. This updated and expanded edition discusses many different tools for root cause analysis and presents them in an easy-to-follow structure: a general description of the tool, its purpose and typical applications, the procedure when using it, an example of its use, a checklist to help you make sure if is applied properly, and different forms and templates (that can also be found on an accompanying CD-ROM). The examples used are general enough to apply to any industry or market. The layout of the book has been designed to help speed your learning. Throughout, the authors have split the pages into two halves: the top half presents key concepts using brief languagemdash;almost keywordsmdash;and the bottom half uses examples to help explain those concepts. A roadmap in the margin of every page simplifies navigating the book and searching for specific topics. The book is suited for employees and managers at any organizational level in any type of industry, including service, manufacturing, and the public sector.
Keywords: Total quality management; Problem solving; Quality control; Textbooks; Global Business Dynamics (BIN2043-N)